Unifying the canonical, historical, and play-by-play present - Anand, Pranav; Toosarvandani, Maziar (Proceedings of Sinn und Bedeutung, 2019)
While the present tense is typically taken to index the reference time to the time of utterance, such a restriction cannot capture noncanonical uses of the present in English, such as the historical present or play-by-play present. We adopt a bicontextual semantics for present tense, in which the two time coordinates are mediated by pragmatics, allowing us to bring canonical, narrative, and play-by-play uses under a single denotation. Moreover, we show that such a treatment can also capture the novel observation that the historical use of the present tense can “anchor” the past perfect, while its other two uses cannot.